Telicity, durativity, and secondary imperfective verbs in Bulgarian - Elena Karagjosova (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The article argues against earlier treatments of Bulgarian secondary imperfective verbs in terms of atelicity and Viewpoint imperfectivity. Instead, it offers empirical evidence about telicity and durativity as the two core properties of this type of verbs in Bulgarian aspectual triplets. An analysis is proposed in terms of Rothstein’s (2004) aspectual classes as properties of verbal predicates that captures the way secondary imperfective verbs differ from both their bare imperfective and perfective counterparts. At the same time, the analysis captures the intrinsic semantic relationship between the triplet members and accounts for the role of the aspectual morphology in terms of aspectual operators that shift the aspectual properties of verbal stems.